National Nature Park “Dvorichanskyi”: a history of establishment and start - Атемасова, Т. А.; Токарський, В. А.; Височин, М. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
A brief history of the National Nature Park “Dvorichanskyi” is presented. Chalky hills in the Oskol valley that include unique and rare flora are a priority for conservation in a newly established national park. The project ofestablishing the national nature park is based on long-term studies carried out by researchers of the KarazinKharkiv National University (Kharkiv). 28 plant species and 32 animal species that are listed in the Red Data Book of Ukraine inhabit the NNP “Dvorichanskyi” territory. Also, there are 17 types of rare habitats in the park. An expansion of the park territory is planned.